Evaluation of tomato (Lycopersicon esculentum, Mill) in greenhouse conditions: phenological and physiological criteria. - Santiago, Josafad (2016)
The objecti ves of this research are to evaluate the best tomato genotypes, according to their vegetative cycle, yield, and fruit quality, and to determine the influence of photosynthesis, transpiration and efficient water use. This work started in October, 1993, and ended in 1994; it was carried out under greenhouse conditions, at the Universidad Autónoma Agraria "Antonio Narro", Saltillo, Coabuila, Mexico. Significant differences were found among samples between genotypes, time of day, and leaf position. Genotypic yield was influenced by temperature: there was flower drop. The Celebrity genotype of determinate growth habit showed the highest yield per plant (5.42 kg/pt), and was also the most efficient with respect to water use, needing only 22.5 liters to produce a kilogram of fruit. The most precocious hybrid was the determined growth habit Bingo.